Can the feel of the haptic interaction modify a user's emotional state - Gatti, E; Caruso, G; Bordegoni, M; Spence, C (2013)
Haptic perception constitutes an important component of our everyday interaction with many products. At the same time, several studies have, in recent years, demonstrated the importance of involving the emotions in the user-product interaction process. The present study was designed to investigate whether haptic interactions can affect, or modulate, people's responses to standardized emotional stimuli. 36 participants completed a self-assessment test concerning their emotional state utilizing as a pointer either a PHANToM device simulating a viscous force field while they moved the stylus, or else a stylus with no force field. During the presentation of the emotional pictures, various physiological parameters were recorded from participants. The results revealed a significant difference in the self-reported arousal associated with the pictures but no significant difference in the physiological measures. The behavioural findings are interpreted in terms of an effect of the haptic feedback on participants' perceived/interpreted emotional arousal. These results suggest that haptic feedback could, in the future, be used to modify participants' interpretation of their physiological states. © 2013 IEEE.